Electrically-inactive phosphorus re-distribution during low temperature annealing - Peral, Ana; Youssef, Amanda; Dastgheib-Shirazi, Amir; Akey, Austin; Peters, Ian Marius; Hahn, Giso; Buonassisi, Tonio; Del Canizo, Carlos (Journal of Applied Physics, 2018)
An increased total dose of phosphorus (P dose) in the first 40 nm of a phosphorus diffused emitter has been measured after Low Temperature Annealing (LTA) at 700 °C using the Glow Discharge Optical Emission Spectrometry technique. This evidence has been observed in three versions of the same emitter containing different amounts of initial phosphorus. A stepwise chemical etching of a diffused phosphorus emitter has been carried out to prepare the three types of samples. The total P dose in the first 40 nm increases during annealing by 1.4 × 1015 cm-2 for the sample with the highly doped emitter, by 0.8 × 1015 cm-2 in the middle-doped emitter, and by 0.5 × 1015 cm-2 in the lowest-doped emitter. The presence of surface dislocations in the first few nanometers of the phosphorus emitter might play a role as preferential sites of local phosphorus gettering in phosphorus re-distribution, because the phosphorus gettering to the first 40 nm is lower when this region is etched stepwise. This total increase in phosphorus takes place even though the calculated electrically active phosphorus concentration shows a reduction, and the measured sheet resistance shows an increase after annealing at a low temperature. The reduced electrically active P dose is around 0.6 × 1015 cm-2 for all the emitters. This can be explained with phosphorus-atoms diffusing towards the surface during annealing, occupying electrically inactive configurations. An atomic-scale visual local analysis is carried out with needle-shaped samples of tens of nm in diameter containing a region of the highly doped emitter before and after LTA using Atom Probe Tomography, showing phosphorus precipitates of 10 nm and less before annealing and an increased density of larger precipitates after annealing (25 nm and less).
CRIS-Team Scopus Importer:2022-06-05